(untitled) (Research, Society and Development, 2020)
Accessibility contributes to a better quality of life, because, through accessible mechanisms, people can have greater social participation and exercise their citizenship. However, the implementation of these mechanisms occurs gradually, since it is possible to observe that not all spaces are able to meet the public that needs environmental adaptations. One of the challenges of universal accessibility is the architectural barriers that exist in the most diverse spaces that imply the limitation of displacement of subjects who have their mobility compromised by physical problems. Thus, this work aimed to identify the accessibility of leisure spaces in the city of Santa Maria, RS for people with physical disabilities. The investigative process was conducted through the application of a questionnaire authored by Ribeiro (2014), adapted for NBR 9050/2015. The result obtained showed that the leisure places in the city have some degree of accessibility, however, it is necessary to make necessary changes to adapt to the requirements of the current standard. Finally, it is possible to conclude that none of the evaluated places is fully in accordance with the most recent standard of accessibility.